DroidBet:event-driven automatic detection of network behaviors for Android applications - Song-jie WEI; Gao-xiang WU; Na LUO; Zhao-wei SHI; Zi-yang ZHOU (Tongxin xuebao)
The most Android applications connect to Internet to communicate with the outside world.Applications’ network-related activities were reflected and described with network traffic.By analyzing and modeling network traffic of Android applications,network behaviors of Android applications could be subsequently characterized.Therefore,DroidBet:an event-driven network behavior automatic detection system was presented,to test and evaluate Android applications automatically.Firstly,a scenario simulation event library was built to simulate the events that applications may be executed in the process,so as to trigger the network behavior of the application as much as possible.Then,the test sequence based on the state transition analysis method was automatically generated,and the network behavior was dynamically collected during the application testing process.Finally,the machine learning method was used to learn and train the collected network behavior,and the network behavior model based on BP neural network was generated to detect the behavior of the unknown Android application.The experimental results show that DroidBet can effectively trigger and extract the network behavior of the application,which has the advantages of high accuracy and low resource cost.